Building Osteogenic Microenvironments With Strontium-Substituted Calcium Phosphate Ceramics - Wan, Ben; Wang, Renxian; Sun, Yuyang; Cao, Jingjing; Wang, Honggang; Guo, Jianxun; Chen, Dafu (Frontiers in Bioengineering and Biotechnology, 2020)
Bioceramics have experienced great development over the past 50 years. Modern bioceramics are designed to integrate bioactive ions within ceramic granules to trigger living tissue regeneration. Preclinical and clinical studies have shown that strontium is a safe and effective divalent metal ion for preventing osteoporosis, which has led to its incorporation in calcium phosphate-based ceramics. The local release of strontium ions during degradation results in moderate concentrations that trigger osteogenesis with few systemic side effects. Moreover, strontium has been proven to generate a favorable immune environment and promote early angiogenesis at the implantation site. Herein, the important aspects of strontium-enriched calcium phosphate bioceramics (Sr-CaPs), and how Sr-CaPs affect the osteogenic microenvironment, are described.